Hubungan antara Tingkat Religiusitas dan Pengendalian Diri pada Remaja Tingkat SMA - Esti Listiari (LPPM Universitas Proklamasi 45, 2011)
Objective of this research is to understand the relationship between adolescence's religious level and their self-control. Adolescence with higher in their religious level tend to have more internal self-control. They will assertively reject their peers when the peer's decision is not in line with them. Fifty senior high school students participate in this research. Those students are motivated to fill in two scales i.e. the religious scale and the self-control scale. This research revealed that there is strong relationship between religious level and self-control among high school students (r= .624). Religious may become a good protection for adolescence for doing erroneously.